Accident Prevention and Traffic Control at Hill Stations using Machine Learning & IoT - Loganathan, E.; Nithyananthan, N.; NanthaKumar, K.; Murad, MD Rahil (Journal of ISMAC, 2024)
Accidents are a prevalent concern in hilly areas, particularly at hairpin bends, leading to both traffic congestion and endangering human lives. When a vehicle becomes stranded or an accident occurs at a hairpin bend, it often results in frustrating traffic jams that hinder the resolution of the issue and the management of the accident. These challenges are particularly troublesome in hilly regions and pose difficulties in accident prevention and traffic control. To tackle these issues, the study seeks to offer a comprehensive solution to mitigate these drawbacks. We have conducted a thorough analysis of various research papers and have identified effective methodologies to address the unique challenges presented by hairpin bends in hilly terrains. By employing these proven methodologies, the primary objective of the study is to save lives, prevent accidents, and efficiently manage traffic in hilly areas. By implementing these solutions, we aim to make travel in hill stations safer and more efficient. This includes reducing the risks associated with accidents and alleviating the inconveniences caused by traffic congestion at hairpin bends.